2018
DOI: 10.3892/ijmm.2018.3575
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aberrantly expressed long non-coding RNAs in postmenopausal osteoporosis

Abstract: Postmenopausal osteoporosis (PMOP) is a common skeletal disorder in postmenopausal women. The present study aimed to identify the key long non-coding RNAs (lncRNAs) in PMOP through RNA sequencing. RNA sequencing was performed to obtain the expression profile of lncRNAs and mRNAs in blood samples of patients with PMOP and normal controls (NCs). Following the identification of differentially expressed mRNAs (DEmRNAs) and differentially expressed lncRNAs (DElncRNAs), the DElncRNA-DEmRNA co-expression network was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…Recent studies have reported that lncRNAs could act as key regulators of osteogenic differentiation and pathological processes of osteoporosis 28 . Fei et al reported that 51 lncRNAs were differentially expressed in patients with osteoporosis compared with healthy controls 29 . Shen et al showed that the expression of lncRNA HOTAIR in osteoporosis patients was significantly higher than that in normal people.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that lncRNAs could act as key regulators of osteogenic differentiation and pathological processes of osteoporosis 28 . Fei et al reported that 51 lncRNAs were differentially expressed in patients with osteoporosis compared with healthy controls 29 . Shen et al showed that the expression of lncRNA HOTAIR in osteoporosis patients was significantly higher than that in normal people.…”
Section: Discussionmentioning
confidence: 99%
“…It was commonly known that lncRNAs and miRNAs could bind to each other and exert biological functions in multiple types of human cancers [5,9]. Firstly, our study from bioinformatics predicted the shared binding sites between FTX and miR-137.…”
Section: Discussionmentioning
confidence: 97%
“…Several lncRNAs are differentially expressed in patients with osteoporosis and have been involved in the pathogenesis of this disease; however, additional studies with replication cohorts and larger samples are needed to support these findings. Using high-throughput RNA sequencing, Fei et al ( 64 ) identified 51 lncRNAs that were differentially expressed in patients with PMOP compared with healthy controls. These lncRNAs, including LINC00963, LOC105376834, LOC101929866, LOC105374771, and LOC100506113, may contribute to the pathogenesis of PMOP by regulating the expression of nearby and co-expressed differentially expressed mRNAs and the pathway of osteoclast differentiation.…”
Section: Sources and Functions Of Lncrnasmentioning
confidence: 99%